Fontes de ruídos em unidade neonatal sob a ótica dos profissionais de saúde - Casimiro , Cintia Freitas; Pires , Bruna Hellen Vaz (Revista Saúde & Diversidade, 2019)
Introduction: Loud noises in neonatal units negatively influence the development of the newborn, especially if it is premature, so it is essential that the health team promotes a peaceful environment, with little amount of sound and light stimuli. Objective: To know the perception of health professionals working in a neonatal unit about the sources of noise in this environment. Methods: This is a descriptive research with a qualitative approach conducted with 24 health professionals during the months of May to July 2019 in the city of Boa Vista - RR. In the data analysis, the sequence of steps recommended by Bardin was adopted. Results: The results show that the main sources of noise present in the unit are due to equipment and work dynamics, conversations between professionals and other sources, such as the crying of the newborn and high flow of people passing through the sector. Conclusion: It is necessary to implement in the neonatal unit measures to reduce noise, such as periodic maintenance of equipment and education activities with the health team.